HELICOBACTER PYLORI INFECTION IN CHILDREN PRESENTING WITH RECURRENT ABDOMINAL PAIN: H- Pylori Infection in Children - Punhal, Muhammad; Malik, Qudratullah; Iqbal, Amjad (Pakistan Armed Forces Medical Journal, 2016)
Objective: To determine the frequency of Helicobacter Pylori (H. pylori) infection in children presenting with recurrent abdominal pain (RAP). Study Design: Descriptive cross-sectional study. Place and Duration of Study: This study was conducted at Combined Military Hospital (CMH) Quetta over a period of 10 months from 01-08-2011 to 31-05-2012. Material and Methods: A total of 83 children with recurrent abdominal pain were included in this study. Blood samples of patients were analyzed in laboratory of CMH Quetta for H. pylori Antibody (Ab) titers. Results: Mean age of the patients was 8.12±3.46 years. Distribution of gender showed that 44 patients (53.1 %) were male while 39 patients (46.9 %) were female. Mean duration of symptoms was 15.8%±3.7 months. H. pylori infection was present in 27 (32.5%) patients. Topical ciprofloxacin is more effective in earlier control of congestion and discharge of ear in CSOM; (p value <0.001 and <0.005 respectively) as compared to Neomycin. Conclusion: H. pylori infection is common in children with RAP and presentation of epigastric pain in these patients can be considered as a warning sign to screen for H. pylori infection.